A numerical comparison among different solutions for the design of a rotary elastocaloric prototype. (25th June 2023) - Cirillo, Luca; Greco, Adriana; Masselli, Claudia
Highlights: The elastoCaloric effect as the new frontier of solid-state refrigeration for air conditioning. Nitinol wires as elastoCaloric material cyclic trained to stabilize the mechanical response. Development of 2-D model to predict the thermal-fluid-dynamic behaviour of an elastoCaloric device. Energy performances of the device as results of the investigation by varying operating conditions. Abstract: Among the various emerging proposals in the scientific literature, the class of solid-state refrigeration techniques based on the caloric effect is particularly important. In caloric cooling, there are three types of technology: magnetocaloric, electrocaloric and mechanocaloric, each referring to the field applied to a material which is respectively magnetic, electric or mechanical. The paper presents the results of a detailed analysis to draw a guide map for efficiently designing the first Italian elastoCaloric prototype. It was possible to compare different geometries through a numerical model to optimize the geometric and operational parameters before to construct a rotary elastoCaloric prototype. In this work, the results of numerical simulations are presented in terms of temperature drop on cold side and cooling power. It was also possible to give useful indications in terms of the prototype's efficiency through the evaluation of the coefficient of performance. The best results obtained are: 21.5 K as temperature drop on cold in the cold regenerator, 538 W as cooling power with a COP greater than 6.